2014
DOI: 10.1016/j.fishres.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Self-imposed length limits in recreational fisheries

Abstract: a b s t r a c tA primary motivating factor on the decision to harvest a fish among consumptive-orientated anglers is the size of the fish. There is likely a cost-benefit trade-off for harvest of individual fish that is size and species dependent, which should produce a logistic-type response of fish fate (release or harvest) as a function of fish size and species. We define the self-imposed length limit as the length at which a captured fish had a 50% probability of being harvested, which was selected because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…tial component to the harvest-release decision, and the relationship was similar across species. Past assessments have assumed that fish harvest follows a linear or logistic relationship with fish size (Chizinski et al 2014). We revealed that harvest is more likely to follow a polynomial relationship with fish size and that predict-ing the harvest-release outcome for larger fish is difficult.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…tial component to the harvest-release decision, and the relationship was similar across species. Past assessments have assumed that fish harvest follows a linear or logistic relationship with fish size (Chizinski et al 2014). We revealed that harvest is more likely to follow a polynomial relationship with fish size and that predict-ing the harvest-release outcome for larger fish is difficult.…”
Section: Discussionmentioning
confidence: 78%
“…this assertion, with fish size contributing most to gain and coverage importance in the harvest-release model. Previous work predicted that a threshold exists (i.e., self-imposed length limit) as to when a fish will be released or harvested (Chizinski et al 2014). Fish below this threshold will likely be released and fish above this threshold will likely be harvested, thus balancing the costs and trade-offs of harvest with respect to fish size (Chizinski et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each subgroup of anglers can vary in their specialization, motivations, choice of species targeted, angling method, and tackle choices, among a multiplicity of other factors. Thus, during any given period at a waterbody there is a heterogeneous suite of anglers fishing for a multitude of species (Chizinski et al 2014a(Chizinski et al , 2014b, using various gears and approaches (e.g., angling from a boat or bank). Furthermore, no angling tackle or bait is exclusive to the species being targeted.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract this, some countries have modified their fishing regulations to promote the release of females (Jonsson and Jonsson 2011). Managers often emphasize the beneficial and deleterious aspects of minimum-length limits or catch-and-release regulations to overcome the overexploitation of fish stocks and fisheries (e.g., Arlinghaus et al 2007;Allen et al 2009;Chizinski et al 2014). However, sustainable fisheries may be achieved by nontraditional harvest regulations such as stabilizing harvest-slot limits (Arlinghaus et al 2010;Gwinn et al 2015) or by restricting fishing of a particular sex (usually to protect females) (Jonsson and Jonsson 2011).…”
mentioning
confidence: 99%